The Relationship between Self-efficacy and Academic Stress among College Students - Rossanti, Tariza; Mudhar, Mudhar (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to analyze the relationship between self-efficacy and academic stress among students of the Guidance and Counseling Study Program at Universitas PGRI Adi Buana Surabaya from the 2021 and 2022 cohorts. The research employed a quantitative approach with a correlational design involving 72 students. The research instruments consisted of a self-efficacy scale and an academic stress scale. At the same time, data analysis was conducted using the Pearson Product-Moment correlation test with the aid of SPSS version 26. The results revealed a significant negative relationship between self-efficacy and academic stress, with a correlation coefficient (r) of -0.582 and a significance value (p) of 0.00 (<0.05). This indicates that the higher the students’ self-efficacy, the lower their level of academic stress. Conversely, students with lower self-efficacy tend to experience higher academic stress. This study concludes that self-efficacy is important in reducing academic stress among students. The implications of thesefindings highlight the crucial role of academic advisors and educational counselors in designing guidance programs and psychological interventions to enhance students’ self-efficacy as a preventive measure against academic stress.